"Diverso do que é": negociações sobre o diagnóstico de "doença mental" em conversações intra-familiares - Lisboa, Milena Silva (2008)
Labeling a person as mentally ill is an extremely complex and controversial process, involving social concepts and psychiatric knowledge about mental illness . The analysis of the process through which Psychiatry captured, historically, the notion of madness and still grasps and encloses it allows us to comprehend the related and social nature of mental illness . Labeling Theory considers mental illness as a historically constructed label, imputed to those who present deviant behavior, whose performances violate established patterns of sociability. Through psycho-sociological reflections about the recognition process of deviations such as mental illness , this research proposes to analyze the ways in which family members conversationally negotiate meaning faced with social rule-breaking and the later labeling process. Labeling Theory and Conversational Analysis offer theoretical and methodological tools to approach daily family conversations, considering how important moments of the social labeling process are dealt with conversationally. Interviews and free form meetings were carried out with the family of a person who had recently initiated the labeling process of mental illness . The family s ethno-methods were stressed, pointing out the different patterns of interaction constructed dialogically by the participants when referring to different moments of the labeling process. The results suggest that the social labeling of the participant was still taking place and, within this process, new meanings were elaborated daily by the family in its interactions. Despite resistance to labeling which emerged in defense of macumba (Afro-Brazilian witchcraft) as an alternative label, the family s comprehension about his suffering started to be referred to by the label of depression , in an approximation of psychiatric comprehension. These a posteriori re-elaborations suggest that social actors converse retroactively about social labeling moments, reconstructing meaning at each interaction. Such gradual and dynamic construction points to the importance of conversation in elaborating a self marked by the stigma involved in the label of mentally ill or, alternatively, to the elaboration of new comprehensions based on the acceptance of differences and care